PENGETAHUAN REMAJA PUTRI TENTANG BAHAYA PERNIKAHAN DINI PADA KEHAMILAN DI DUSUN PINANG LOMBANG BAWAH DESASEI RAJA KECAMATAN NA IX-X KABUPATEN LABUHANBATU UTARA 2017 - Fitriyani - Nasution (Akademi Kebidanan Ika Bina, 2018)
Pap smears are examinations of mucus in the mouth of the uterus, the purpose of pap smears To detect early risk of cervical cancer. According to WHO data that about 500,000 women are treated annually with cervical cancer. In Indonesia it is estimated that around 40% of cases per day and 50% of them died of the disease. According to data 83% of patients with cervical cancer are in developing countries.510,000 women are diagnosed with cervical cancer .280,000 and nearly 60% of them die. The incidence is around 74% compared to other gynecological cancers. This type of research is a descriptive study that aims to describe the knowledge of fertile age couples (wives) about Pap smears in the environment like Dame. Data that is used primary data is directly from respondents, and using secondary data is data that is not taken directly from respondents, independent population variables are based on age, education, occupation, sources of information. The dependent variable is the knowledge of fertile age couples about Pap smears in the environment Suka Dame. Based on the knowledge of fertile age couples about the majority of Pap smears with less knowledge of 24 respondents (41.38%), the knowledge of fertile age couples based on the age of 4346 years, the majority of knowledge is less than 3 respondents (5.17%). lack of secondary education as many as 12 respondents (20.69%). The majority of knowledgeable respondents were not working at 21 respondents (36.21%). Respondents with less knowledge on respondents who did not get as many as 7 respondents (12.06) From the variables studied based on knowledge. Age. Education. work. The source of information can be concluded that the knowledge of fertile age couples about the Pap smear is in the less category, to be expected to fertile age couples (wives) so as to prevent kesaktitan and also death in couples of childbearing age (wives) in particular. Based on the results of research conducted based on knowledge , age of education, occupation, source of information can be concluded that Knowledge of Fertile Age Couples (wives) About knowledgeable Pap smears are lacking.